Steady-state thermal hydraulic modelling and turbine trip transient simulation of the NuScale integral pressurised water reactor using the ASTEC code - Guo, Zhexi; Xiao, Sicong; Chung, Keng Yeow (Frontiers in Energy Research, 2022)
Using the thermal hydraulic module CESAR of the severe accident code ASTEC, a steady state model of the NuScale reactor has been built. Considering that there is not much work in this area using ASTEC, the code’s capabilities could be verified in the process from a user’s point of view. Construction of the model was achieved through iterations based on convergence towards data provided by NuScale pertaining to the most crucial operating properties at not just full nominal power but also at lower power levels. The model was verified by agreement of quantities such as core temperatures, coolant mass flow rate and secondary steam temperature at all operating powers with reference values to within 3% deviation. With a similar methodology, the previous model was adjusted to give a second steady state model meant to provide conservative initial conditions from which a turbine trip transient simulation would be performed. Agreement with literature was again good, with maximum deviations of less than 1.8 % for monitored parameters. Lastly, a turbine trip transient was simulated and compared to reference data from analyses performed with NRELAP5 and RELAP5/SCDAPSIM. Most important system behaviors are well captured and reproduced, with discrepancies arising from inevitable estimates made due to lack of information.